Improving early literacy through teacher professional development: Experimental evidence from Colombia - Horacio Alvarez Marinelli; Samuel G. Berlinski; Matias Busso; Julian Martinez-Correa (Journal of Public Economics Plus, 2023)
Teachers are a fundamental input for classroom learning. Consequently, teacher development is a policy priority for governments around the world. We experimentally evaluate the effectiveness of ''Let's All Learn to Read,'' a curricular reform implemented via a one-year professional development program that trained and coached first-grade teachers throughout the school year and provided them and their students with structured materials. Following a year of instruction by trained teachers, students' literacy scores in treated schools grew by 0.39 of a standard deviation compared to students in the control group. These gains persisted after the intervention finished; through the second and third grades.
Keywords: I20; H52; O15; 330; Teacher professional development; Early Interventions; Literacy; Colombia